2010
DOI: 10.1108/10595421011080760
|View full text |Cite
|
Sign up to set email alerts
|

Trade protectionism: reasons and outcomes

Abstract: Purpose -The purpose of this paper is to establish the benefits of free trade, to examine the reasons and outcomes of protectionist policies, and to evaluate the rationale behind trade protectionism. Design/methodology/approach -The methodology used in this paper includes review of the literature and empirical studies published from 1967 to 2008, and descriptive statistical analysis of data published by international organizations. Findings -International trade has been growing faster than growth of world gros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 11 publications
0
37
0
1
Order By: Relevance
“…It has been shown that all countries, with both young and developing democracies, as well as old and developed ones, are likely to suffer from rules and regulations that are passed by the minority who have won the elections (Hashmi, 2018). For instance, it has been shown that free trade agreements are for the profit of all nations, protectionist laws in the US are enacted to further restrict free trade in favor of only some industries and at a loss to the public (Abboushi, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that all countries, with both young and developing democracies, as well as old and developed ones, are likely to suffer from rules and regulations that are passed by the minority who have won the elections (Hashmi, 2018). For instance, it has been shown that free trade agreements are for the profit of all nations, protectionist laws in the US are enacted to further restrict free trade in favor of only some industries and at a loss to the public (Abboushi, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Fall 2019 25 quotas, that have been enacted by politicians to support a small group's interests rather than supporting the public's welfare (Abboushi, 2010;Hill & Hult, 2018). Under such conditions, owners of certain industries would support candidates that had pro-protectionist trade laws (Abboushi, 2010), and the owners would, in turn, fund their political campaigns to win (Applyard & Field, 2014). It is worthy to note that such interest groups' investments in funding political campaigns are always less than the expected returns from that policy (Appleyard & Filed, 2014).…”
Section: How Small Interest Groups Can Influence Political Outcomesmentioning
confidence: 99%
“…Implementing trade measures can be also explained by infant industry argument and strategic trade policy theory. Emerging new industry (infant industry) is protected by the application of production subsidies on domestic production, as well as by imposing tariffs on imports and import quotas which should be reduced over the time [51][52][53][54][55][56]. Strategic interactions between the firms influence on active government intervention and create an opportunity for the government's action.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, their campaign funding contributions could attract a candidate's attention in terms of considering supporting the funding groups' views in the future, a rent seeking activity, as the small interest group would bear some costs that could be used for future benefits from a policy (Appleyard & Field, 2014). For instance, the results of such activities have been many protectionist trade policies, such as tariffs and quotas, that have been enacted by politicians to support a small group's interests rather than supporting the public's welfare (Abboushi, 2010;Hill & Hult, 2018). Under such conditions, owners of certain industries would support candidates that had pro-protectionist trade laws (Abboushi, 2010), and the owners would, in turn, fund their political campaigns to win (Applyard & Field, 2014).…”
Section: How Small Interest Groups Can Influence Political Outcomesmentioning
confidence: 99%
“…For instance, the results of such activities have been many protectionist trade policies, such as tariffs and quotas, that have been enacted by politicians to support a small group's interests rather than supporting the public's welfare (Abboushi, 2010;Hill & Hult, 2018). Under such conditions, owners of certain industries would support candidates that had pro-protectionist trade laws (Abboushi, 2010), and the owners would, in turn, fund their political campaigns to win (Applyard & Field, 2014).…”
Section: How Small Interest Groups Can Influence Political Outcomesmentioning
confidence: 99%